Validation and clinical application of a nested PCR for paracoccidioidomycosis diagnosis in clinical samples from Colombian patients (2015)
ABSTRACT: Paracoccidioidomycosis is a systemic and endemic mycosis, restricted to tropical and sub-tropical areas of Latin America. The infection is caused by the thermal dimorphic fungusParacoccidioides brasiliensis and Paracoccidioides lutzii. The diagnosis of paracoccidioidomyco-sis is usually performed by microscopic examination, culture and immunodiagnostic teststo respiratory specimens, body fluids and/or biopsies; however these methods require labo-ratory personnel with experience and several days to produce a result. In the present study,we have validated and evaluated a nested PCR assay targeting the gene encoding the Para-coccidioides gp43 membrane protein in 191 clinical samples: 115 samples from patients withproven infections other than paracoccidioidomycosis, 51 samples as negative controls, and25 samples from patients diagnosed with paracoccidioidomycosis. Additionally, the speci-ficity of the nested PCR assay was also evaluated using purified DNA isolated from culturesof different microorganisms (n = 35) previously identified by culture and/or sequencing. Theresults showed that in our hands, this nested PCR assay for gp43 protein showed specificityand sensitivity rates of 100%. The optimized nested PCR conditions in our laboratory alloweddetection down to 1 fg of P. brasiliensis DNA.